1987
DOI: 10.1111/j.1651-2227.1987.tb10416.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Enzyme Supplementation as Acid‐Resistant Microspheres versus Enteric‐Coated Granules in Cystic Fibrosis

Abstract: In order to compare the efficacy of pancreatic enzyme supplementation as pH-sensitive enteric-coated microspheres Pancrease to that of conventional supplementation with enteric-coated Pancreatin in cystic fibrosis, a double blind cross-over study was conducted. Eleven patients under 12 years of age received each of the enzyme preparations for four weeks. Treatment efficacy was evaluated by means of a symptom score card recording stool frequency, consistency, colour, odour, abdominal cramps and appetite as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…There were no drug-related SAEs or discontinuations, nor were there any incidences of hyperuricemia or unexpected adverse trends in laboratory analyses following treatment with EUR-1008. As with previous studies of PEPs in young children [22][23][24][25][26], no age-related issues were noted with EUR-1008. However, these safety data may be limited by the short length of the study period (two weeks), which is too brief to detect AEs such as fibrosing colonopathy (not observed in this study).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…There were no drug-related SAEs or discontinuations, nor were there any incidences of hyperuricemia or unexpected adverse trends in laboratory analyses following treatment with EUR-1008. As with previous studies of PEPs in young children [22][23][24][25][26], no age-related issues were noted with EUR-1008. However, these safety data may be limited by the short length of the study period (two weeks), which is too brief to detect AEs such as fibrosing colonopathy (not observed in this study).…”
Section: Discussionsupporting
confidence: 55%
“…This is significant, as weight loss during infancy or childhood correlates with poor adult pulmonary status in CF patients [5][6][7][8][9][10][11]. The decision to not use a placebo treatment or washout period in the design of the supplemental study is consistent with the practice reported in other published trials involving young CF patients [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Young children achieve sufficient growth and weight gain more easily when only small amounts of fat and energy are lost in the stool. Increases in weight were larger during treatment with an acid resistant enzyme preparation than after an uncoated pancreatin formulation [18]. The present study with 4 weeks duration demonstrated no loss of body weight with either treatment but was too short to evaluate body weight development for clinical relevance.…”
Section: Discussionmentioning
confidence: 45%
“…Here we compare our cross-sectional data for CF populations aged 1 to 9 years in 2002 and discuss their outcomes in the context of NBS studies performed elsewhere. [9][10][11][12] We focused on patients in whom CF was diagnosed after 1994 who were treated with acid resistant enzymes 19 and determined whether NBS afforded any significant clinical benefit.…”
mentioning
confidence: 99%